The Invisible Life of Addie LaRue - Schwab, Victoria (New York : Tor, 2020)
Making a Faustian bargain to live forever but never be remembered, a woman from early eighteenth-century France endures unacknowledged centuries before meeting a man who remembers her name.
Keywords: Memory -- Fiction; Immortalism -- Fiction; Fantasy fiction; Historical fiction